2021
DOI: 10.1097/mpg.0000000000003373
|View full text |Cite
|
Sign up to set email alerts
|

Is Roux‐en‐Y Feeding Jejunostomy a Safe and Effective Operation in Children? A Systematic Review Exploring Outcomes

Abstract: Objectives: Roux-en-Y jejunostomy (REYJ) may establish feeding in children with foregut dysmotility or severe gastro-esophageal reflux disease (GERD). Nevertheless, concerns have been raised about safety and efficacy. We, therefore, evaluated outcomes of REYJ by systematic review to determine if this was a satisfactory option for achieving enteral autonomy in children with complex nutritional needs. Methods: A PRISMA-adherent systematic review was conducted of studies reporting children undergoing feeding REYJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Investigations may overlap with those done as part of fundoplication assessment. An upper gastrointestinal contrast study may be considered to exclude mechanical obstruction 1,20 . The indication for upper gastrointestinal endoscopy prior to JT feeding varies depending on individual patient circumstances, and in children with unexplained intolerance to gastric feeding or significant gastrointestinal symptoms, it may be helpful to exclude underlying mucosal inflammation or malabsorptive disorders 1 .…”
Section: Recommendations and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigations may overlap with those done as part of fundoplication assessment. An upper gastrointestinal contrast study may be considered to exclude mechanical obstruction 1,20 . The indication for upper gastrointestinal endoscopy prior to JT feeding varies depending on individual patient circumstances, and in children with unexplained intolerance to gastric feeding or significant gastrointestinal symptoms, it may be helpful to exclude underlying mucosal inflammation or malabsorptive disorders 1 .…”
Section: Recommendations and Discussionmentioning
confidence: 99%
“…gastrointestinal contrast study may be considered to exclude mechanical obstruction. 1,20 The indication for upper gastrointestinal endoscopy prior to JT feeding varies depending on individual patient circumstances, and in children with unexplained intolerance to gastric feeding or significant gastrointestinal symptoms, it may be helpful to exclude underlying mucosal inflammation or malabsorptive disorders. 1 A review of results of preoperative evaluation done at the time of GT insertion found that no specific diagnostic test reliably predicted whether patients remained on GT feeding or required conversion to JT feeding.…”
Section: Journal Of Parenteral and Enteral Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…More publications about open Roux-en-Y jejunostomy are available. Recently, a systematic review comparing these publications was published [ 20 ]. Open surgery is associated with a different type (more severe) and a higher rate of complications compared to the LRFJ, as there is a high (6–40%) incidence of wound infections [ 17 , 23 , 24 ] and volvulus (14–25%) [ 24 26 ] compared to respectively 8% and 0% in our patient population.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated by a recent systematic review evaluating the outcomes of Roux-en-Y jejunostomy in the pediatric population, more data regarding the outcomes of LRFJ are lacking in current literature. All but one of the included studies evaluated the outcomes in children undergoing open Roux-en-Y jejunostomy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%